Assessment of the dynamics of innovation in the Republic of Kazakhstan, scientific and technical activities - Al’zhanova F.G., Myrzashov N. (Journal of Economic Research & Business Administration, 2016)
Currently, to solve the problem of achieving economic growth in Kazakhstan is closely connected with the accelerated development of innovative sphere. Meeting the challenges facing the economy of Kazakhstan in the transition to a qualitatively new stage – a sustainable recovery – can be achieved by innovation-oriented development. In this article, we studied the theoretical aspects of evaluation of innovation country. This assessment was conducted on the basis of indicators of the degree of innovation activity. In addition, given the direction of stimulation of innovative activity in the country.